Advances in sample preparation for membrane proteome quantification. (December 2021) - Masuda, Takeshi; Ito, Shingo; Ohtsuki, Sumio
Graphical abstract: Abstract : Membrane proteins mediate various biological processes. Most drugs commercially available target proteins on the cell surface. Therefore, proteomics of plasma membrane proteins provides useful information for drug discovery. However, membrane proteins are one of the most difficult biological groups to quantify by proteomics because of their hydrophobicity and low protein content. To obtain unbiased quantitative membrane proteomics data, specific strategies should be followed during sample preparation. This review explores the most recent advances in sample preparation for the quantitative analysis of the membrane proteome, including enrichment by subcellular fractionation and trypsin digestion.